2013
DOI: 10.4238/2013.september.10.2
|View full text |Cite
|
Sign up to set email alerts
|

Association between the TRAIL single nucleotide polymorphism rs1131580 and type 2 diabetes mellitus in a Han Chinese population

Abstract: ABSTRACT. Tumor necrosis factor (TNF)-related apoptosis-inducing ligand (TRAIL) is expressed in different tissues and cells, including the pancreas and lymphocytes, and it can selectively induce apoptosis in tumor cells but not in most normal cells. TRAIL plays critical roles in type 1 diabetes mellitus, and is involved in type 2 diabetes mellitus (T2DM). We recently discovered the association of nonalcoholic fatty liver disease, a risk factor for T2DM, with a single nucleotide polymorphism (SNP) in the TRAIL … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…T2DM is a complex disease affected by both genetic and environmental factors ( Gujral et al, 2013 ). Many genetic association studies have suggested that several genes and specific SNPs are associated with risk of T2DM ( Nair et al, 2012 , Ng et al, 2008 , Rai et al, 2012 , Yu et al, 2013 ). In fact, TCF7L2 is considered the most influential gene in determining genetic susceptibility for T2DM in humans ( Luo et al, 2009 , Ng et al, 2008 , Qiao et al, 2012 , Wang et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…T2DM is a complex disease affected by both genetic and environmental factors ( Gujral et al, 2013 ). Many genetic association studies have suggested that several genes and specific SNPs are associated with risk of T2DM ( Nair et al, 2012 , Ng et al, 2008 , Rai et al, 2012 , Yu et al, 2013 ). In fact, TCF7L2 is considered the most influential gene in determining genetic susceptibility for T2DM in humans ( Luo et al, 2009 , Ng et al, 2008 , Qiao et al, 2012 , Wang et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that the 3ʹ-UTR region of exon 5 of TRAIL plays an important role in regulation of the TRAIL gene [6,24,35]. The 3ʹ-UTR, which functions as a regulatory region at the level of protein expression, binds not only to mRNA but also to mRNA coated with RNA proteins [RBPs] and microRNAs (miRNAs), which play important roles in the regulation of translation [24,36].…”
Section: Discussionmentioning
confidence: 99%
“…The 3ʹ-UTR, which functions as a regulatory region at the level of protein expression, binds not only to mRNA but also to mRNA coated with RNA proteins [RBPs] and microRNAs (miRNAs), which play important roles in the regulation of translation [24,36]. Studies have suggested that an allelic variation which changes the level of expression of the protein in the genome of patients, particularly in the 3ʹ-UTR, plays an important role in the outcome of the disease [36].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations